Current Advances and Future Directions for Sensitizing Gastric Cancer to Immune Checkpoint Inhibitors - Wenke Li; Menghui Xu; Mo Cheng; Jing Wei; Lin Zhu; Yu Deng; Fukun Guo; Feng Bi; Ming Liu (Cancer Medicine)
ABSTRACT Background Immunotherapy combined with chemotherapy has become the standard treatment for HER2‐negative gastric cancer (GC), but its clinical benefits remain limited, with a median progression‐free survival (mPFS) of 6–8 months and median overall survival (mOS) of 15–18 months. These outcomes are particularly poor in patients with CPS < 1. The marked heterogeneity of GC, along with primary and secondary resistance, presents significant clinical challenges and underscores the urgent need for novel therapeutic strategies. Recent Advances To address these limitations, several combination therapies are being explored. Anti‐VEGF therapy combined with immune checkpoint inhibitors (ICIs) has shown synergistic effects by enhancing immune cell infiltration and reducing tumor‐mediated immunosuppression, thereby improving response rates and survival. Radiotherapy combined with ICIs also holds promise, with low‐dose radiation remodeling the tumor microenvironment and high‐dose radiation inducing immunogenic cell death. Other potential combinations include PD‐1/PD‐L1 inhibitors paired with targeted therapies against HER2, FGFR2, DKK1, PARP, LSD1, HDAC, and other emerging targets. Novel approaches such as hyperbaric oxygen therapy, oncolytic viruses, metabolic modulators, and fecal microbiota transplantation are also under investigation to further enhance immune responses. Conclusion These multimodal strategies represent a promising shift toward personalized, mechanism‐driven immunotherapy sensitization. By targeting diverse pathways to overcome immune resistance, they aim to reshape the tumor microenvironment, restore immune responsiveness, and improve outcomes in GC. While many remain in early‐stage development, accumulating evidence supports their potential. Future research should prioritize optimizing combination regimens, clarifying resistance mechanisms, and identifying predictive biomarkers through multi‐omics and artificial intelligence to enable more precise, individualized immunotherapy.